2017
DOI: 10.1186/s12876-016-0563-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influence of gastric intestinal metaplasia on gastric ulcer healing in Helicobacter pylori–infected patients without atrophic gastritis

Abstract: BackgroundGastric epithelial hyper-proliferation was reported in patients with Helicobacter pylori (H. pylori)–infected gastric mucosa with intestinal metaplasia (IM) changes. In patients with gastric ulcer (GU) and IM, the GU may have a different healing rate in comparison to patients without IM. This study aimed to compare the difference in GU healing between H. pylori–infected patients with IM and those without IM.MethodsWe retrospectively analyzed patients at the Keelung Chung Gung Memorial Hospital during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…The prevalence of intestinal metaplasia in H. pylori -positive patients is 57% in Japanese aged approximately 70 years[ 26 ]. Although we saw no significant association between the severity of intestinal metaplasia and ulcer healing speed in this study, Chen et al[ 27 ] reported that patients with intestinal metaplasia had a higher healing rate of gastric ulcers than those without intestinal metaplasia, suggesting that patients with severe gastric atrophy accompanied by intestinal metaplasia should be considered as likely candidates for ESD-related complication, due to delayed ulcer healing.…”
Section: Discussioncontrasting
confidence: 81%
“…The prevalence of intestinal metaplasia in H. pylori -positive patients is 57% in Japanese aged approximately 70 years[ 26 ]. Although we saw no significant association between the severity of intestinal metaplasia and ulcer healing speed in this study, Chen et al[ 27 ] reported that patients with intestinal metaplasia had a higher healing rate of gastric ulcers than those without intestinal metaplasia, suggesting that patients with severe gastric atrophy accompanied by intestinal metaplasia should be considered as likely candidates for ESD-related complication, due to delayed ulcer healing.…”
Section: Discussioncontrasting
confidence: 81%
“…Besides treatment intensification, TDM also includes the possibility of providing insight for reducing the exposure when needed, by re-establishing the standard dosing interval or dose de-escalation. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these studies have shown that adjusting ADL doses and administration intervals are a clinically powerful and cost-effective strategy. 37,3941 For these reasons, there has been increasing effort by the scientific and medical community in research for the development of novel rapid-test assays and monitoring of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a further meta-analysis (Bayesian network) [ 26 ] involving prokinetics for the treatment of FD, 25 randomized control trials were included with a total of 4473 FD patients who were treated with six different prokinetics or placebo. The authors concluded that TM, metoclopramide, domperidone and mosapride showed better efficacy for the treatment of FD than itopride or acotiamide.…”
Section: Discussionmentioning
confidence: 99%